Battery cells, batteries and electrical devices

By optimizing the composition of the electrolyte, negative electrode sheet and isolation film in the battery cell, the problem of insufficient discharge power in the later stage of discharge is solved, and more efficient discharge performance and longer service life are achieved.

CN118476074BActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480001150.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2024-04-09
Publication Date
2025-03-07
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The discharge power of existing battery cells is poor in the later stage of discharge, making it difficult to meet the demand for efficient discharge.

Method used

By optimizing the composition of the battery cell, including adding lithium hexafluorophosphate in the electrolyte, using carbon-based materials and silicon-carbon composites in the negative electrode sheet, and setting appropriate porosity in the isolation film to reduce the internal resistance of the battery at the end of discharge.

Benefits of technology

It significantly improves the discharge power performance of the battery in the later stage of discharge, extends the service life of the battery, and improves the overall energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118476074B_ABST
    Figure CN118476074B_ABST
Patent Text Reader

Abstract

The present application relates to a battery cell, a battery and an electrical device, wherein the battery cell comprises an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator, wherein the electrolyte comprises a lithium salt, wherein the lithium salt comprises lithium hexafluorophosphate, and the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte is 15% to 20%; the positive electrode sheet comprises a positive electrode collector and a positive electrode film layer disposed on at least one side of the positive electrode collector and containing a positive electrode active material; the negative electrode sheet comprises a negative electrode collector and a negative electrode film layer disposed on at least one side of the negative electrode collector and containing a negative electrode active material, wherein the negative electrode active material further comprises a carbon-based material and a silicon-carbon composite, wherein the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than or equal to 0.3% and less than or equal to 10.0%; and the separator is disposed between the positive electrode sheet and the negative electrode sheet. The discharge power of the battery cell described in the present application can be improved in the later stage of discharge.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Chinese patent application 202311421105.X, filed on October 30, 2023, entitled “Battery Cell, Battery and Electrical Device,” the entire contents of which are incorporated herein by reference.

[0003] This application claims priority to PCT patent application PCT / CN2024 / 084136, entitled “Battery Cell, Battery and Electrical Device”, filed on March 27, 2024, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present application relates to the field of rechargeable and dischargeable batteries, and in particular to a battery cell, a battery and an electrical device. Background Art

[0005] Battery cells have the characteristics of high capacity and long life, so they are widely used in electronic devices such as mobile phones, laptops, battery cars, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. Due to the great progress made in the field of batteries, higher requirements are placed on the performance of battery cells.

[0006] However, currently the discharge power of battery cells in the later stage of discharge is poor. Summary of the invention

[0007] The present application provides a battery cell, a battery and an electrical device. The discharge power of the battery cell described in the present application can be improved in the later stage of discharge.

[0008] In the first aspect, the embodiment of the present application proposes a battery cell, which includes an electrolyte, a positive electrode plate, a negative electrode plate and a separator, the electrolyte includes a lithium salt, the lithium salt includes lithium hexafluorophosphate, and the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte is 15% to 20%; the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector and containing a positive electrode active material; the negative electrode plate includes a negative electrode collector and a negative electrode film layer arranged on at least one side of the negative electrode collector and containing a negative electrode active material, the negative electrode active material also includes a carbon-based material and a silicon-carbon composite, the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than or equal to 0.3% and less than or equal to 10.0%; the separator is arranged between the positive electrode plate and the negative electrode plate.

[0009] Therefore, the embodiment of the present application can reduce the internal resistance of the battery at the end of discharge and improve the discharge power performance by regulating the mass content of the negative electrode active material silicon-carbon composite (the mass content of silicon element in the silicon-carbon composite is not less than 0.3% and less than or equal to 10.0%) and matching it with a suitable electrolyte system (the mass content of lithium hexafluorophosphate is 15% to 20%).

[0010] In some embodiments, the mass content of silicon in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than or equal to 4.0% and less than or equal to 7.0%. The mass content of silicon in the silicon-carbon composite within the above range can further improve the energy density of the battery cell, and because the carbon in the silicon-carbon composite can alleviate the expansion of silicon, the expansion of the silicon-carbon composite will not be too large. It can significantly reduce the internal resistance of the battery at the end of discharge and improve the discharge power performance in combination with the above electrolyte system.

[0011] In some embodiments, based on the total mass of the negative electrode active material, the mass content of the silicon-carbon composite is 0.4% to 14.5%. When the negative electrode active material meets the above mass content of silicon element, the discharge power of the battery at low SOC can be further improved.

[0012] In some embodiments, based on the total mass of the negative electrode active material, the mass content of the silicon-carbon composite is 5.75% to 10%. When the mass content of silicon element meets the above content range, the discharge power at low SOC can be further improved.

[0013] In some embodiments, the carbon-based material includes at least one of artificial graphite and natural graphite.

[0014] In some embodiments, the carbon-based material includes artificial graphite.

[0015] In some embodiments, the electrolyte further comprises a cyclic carbonate, and based on the total mass of the electrolyte, the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is (0.60 to 2.50): 1, and can be optionally (1.00 to 1.65): 1. It is inferred that the possible beneficial effects are as follows: when the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is within the above range, it is beneficial to fully dissociate more lithium ions from the lithium hexafluorophosphate, so that even at the end of the discharge at a low SOC, the electrolyte system can contain more lithium ions, and the lithium ions can be continuously dissociated as the battery reaction proceeds, so as to improve the power performance of the battery.

[0016] In some embodiments, the mass content of the cyclic carbonate is 10% to 41%, optionally 20% to 30%; the cyclic carbonate has a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode active material, which is beneficial to the power performance of the battery at the end of discharge.

[0017] In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.

[0018] In some embodiments, the electrolyte further comprises a linear carbonate, and based on the total mass of the electrolyte, the ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate is (0.9 to 6): 1; optionally (1.5 to 2.65): 1. When the mass content ratio of the linear carbonate to the cyclic carbonate satisfies the above range, it is possible to improve both the viscosity and ionic conductivity of the electrolyte and enhance the kinetic properties of lithium ions.

[0019] In some embodiments, the mass content of the linear carbonate is 35% to 65%; and / or the linear carbonate includes at least one of ethyl methyl carbonate EMC, diethyl carbonate DEC and dimethyl carbonate DMC. The viscosity of the linear carbonate is relatively low, which helps to fully dissolve the high content of lithium hexafluorophosphate and facilitates the rapid migration of lithium ions ionized from the lithium hexafluorophosphate between the positive and negative electrodes. At the same time, the combination of the linear carbonate and the cyclic carbonate also helps to increase the electrochemical stability of the electrolyte system and effectively reduce the side reactions of the electrolyte.

[0020] In some embodiments, the electrolyte further includes fluorinated cyclic carbonates. Fluorinated cyclic carbonates can participate in the formation of SEI films on the surface of negative electrode active materials, improve film components and properties, and effectively protect negative electrode active materials: especially when the negative electrode contains silicon, due to the expansion characteristics of silicon, it is more necessary to optimize the film composition of SEI film formation, and the film composition optimization is regulated by regulating the relative proportion of film-forming additives in the electrolyte. The film formed by the participation of fluorinated cyclic carbonates can improve the flexibility of the SEI film, and can improve the structural collapse caused by the release of a large amount of lithium ions by silicon in a short time at the end of discharge; and fluorinated cyclic carbonates have a certain desolvation ability, which is conducive to the migration of lithium ions, and can improve the DCR at low SOC and increase the discharge power.

[0021] In some embodiments, the fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate FEC, bisfluoroethylene carbonate DFEC, and trifluoropropylene carbonate TFPC; optionally, the fluorinated cyclic carbonate includes monofluoroethylene carbonate FEC.

[0022] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte to the mass content of the silicon element is (0.01 to 9.5): 1, and can be (0.01 to 0.15): 1. The above-mentioned content of the fluorinated cyclic carbonate combined with the negative electrode plate can significantly improve the power performance of the battery cell.

[0023] In some embodiments, based on the total mass of the electrolyte, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.005 to 0.30): 1, and can be optionally (0.005 to 0.03): 1. When the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is within the above range, while taking into account the improvement of the flexibility, ion conductivity and electron conductivity of the SEI film, the DCR can also be reduced, thereby improving the discharge power of the battery.

[0024] In some embodiments, based on the total mass of the electrolyte, the mass content of the fluorinated cyclic carbonate is 0.05% to 5.80%, optionally 0.1% to 1.0%. Since the carbon element in the silicon-carbon composite can effectively alleviate the expansion of the silicon element, the relatively low content of the fluorinated cyclic carbonate can also significantly improve the discharge power performance of the battery cell.

[0025] In some embodiments, the lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate. The fluorine-containing inorganic phosphate and the fluorine-containing inorganic borate can participate in the formation of inorganic components in the SEI film, which is beneficial to improving the ion-conducting and electron-conducting properties of the SEI film, and the interface ion impedance of the formed SEI film is low, which is beneficial to the transmission of lithium ions and can improve the DCR at low SOC.

[0026] In some embodiments, based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic phosphate is 0.05% to 0.50%, and optionally 0.10% to 0.30%. The above content of fluorine-containing inorganic phosphate combined with the negative electrode plate can significantly improve the power performance of the battery cell.

[0027] In some embodiments, the mass content of the fluorine-containing inorganic borate is 0.05% to 0.50%, and optionally 0.10% to 0.30%, based on the total mass of the electrolyte. The above-mentioned content of the fluorine-containing inorganic borate combined with the negative electrode plate can significantly improve the power performance of the battery cell.

[0028] In some embodiments, the fluorine-containing inorganic phosphate includes lithium difluorophosphate LiPO2F2; and / or the fluorine-containing borate includes at least one of lithium tetrafluoroborate LiBF4 and lithium difluorooxalatoborate LiDFOB.

[0029] In some embodiments, the electrolyte further includes an additive, the additive includes at least one of 1,3-propane sultone PS, vinylene carbonate VC and lithium fluorosulfonate LiSO3F; based on the total mass of the electrolyte, the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC and the mass content of lithium fluorosulfonate LiSO3F is (0.050 to 0.300): (0.100 to 0.500): (0.001 to 0.300). The ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC and the mass content of lithium fluorosulfonate LiSO3F is within the above range, and the above components can basically participate in the formation of SEI film on the surface of the negative electrode active material, so that the SEI film can effectively alleviate the expansion of the silicon-carbon composite.

[0030] In some embodiments, the mass content of 1,3-propane sultone PS is 0.1% to 1.0%; and / or the mass content of vinylene carbonate VC is 0.1% to 1.0%; and / or the mass content of lithium fluorosulfonate LiSO3F is 0.1% to 1.0%.

[0031] In some embodiments, the battery cell has a liquid retention coefficient of 1 g / Ah to 2.5 g / Ah, and optionally 1.0 g / Ah to 1.5 g / Ah.

[0032] The liquid retention coefficient of the battery cell can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of the battery cell is within the above range, the electrolyte can have a good infiltration effect on the positive electrode plate and the negative electrode plate; and there is a certain gap between the negative electrode plate and the isolation membrane, which can provide expansion space for the volume expansion of the silicon-carbon composite and reduce the risk of overall bulging of the battery.

[0033] In some embodiments, the porosity of the separator is 30% to 40%. In the battery cell of the present application, the electrolyte has a relatively high viscosity due to the relatively high amount of lithium hexafluorophosphate added; the relatively high porosity of the separator facilitates the electrolyte with a high viscosity to pass through the separator, allowing lithium ions to migrate smoothly.

[0034] In some embodiments, the isolation film includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating includes a heat-resistant layer and an organic layer, the heat-resistant layer is disposed on the surface of the organic substrate, and the organic layer is disposed on the surface of the heat-resistant layer away from the organic substrate. The isolation film, in combination with the electrolyte and the negative electrode sheet, can significantly improve the power performance of the battery cell.

[0035] In some embodiments, the organic layer includes a non-fluorinated polymer. The above-mentioned separator, in combination with the above-mentioned electrolyte and the negative electrode plate, can significantly improve the power performance of the battery cell.

[0036] In some embodiments, the non-fluorinated polymer includes a polyacrylate layer. The above-mentioned separator, in combination with the above-mentioned electrolyte and the negative electrode plate, can significantly improve the power performance of the battery cell.

[0037] In some embodiments, the isolation membrane includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating including a ceramic layer and / or a polyacrylate layer; optionally, the coating includes a ceramic layer and a polyacrylate layer; optionally, the ceramic layer is disposed on the surface of the organic substrate, and the polyacrylate layer is disposed on the surface of the ceramic layer away from the organic substrate. The isolation membrane disposes the polyacrylate layer on the outer surface of the isolation membrane, so that the outer surface of the isolation membrane has a certain degree of flexibility, which can effectively alleviate the volume expansion or contraction of the silicon-carbon composite and improve the overall structural stability of the electrode assembly.

[0038] In some embodiments, the thickness of the organic substrate is 6.6 μm to 7.6 μm. When the thickness of the organic substrate is within the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the separator can be substantially consistent, reducing the risk of deteriorating concentration polarization and improving discharge performance.

[0039] In some embodiments, the coating has a thickness of 1.5 μm to 2.5 μm. When the coating has a thickness within the above range, the transmission rate of lithium ions in the negative electrode sheet and the transmission rate in the separator can be substantially consistent, reducing the risk of deteriorating concentration polarization and improving discharge performance.

[0040] In some embodiments, the positive electrode active material includes a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) Y z Compounds, wherein 0<d≤2.1, 0.6<a<1, 0<b<1, 0<c<1, and 0.6<a+b+c<1, 1.8≤z≤3.5, M element includes at least one element of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce; Y element includes at least one element of O and F. The above-mentioned positive electrode active material system, in combination with the above-mentioned electrolyte and negative electrode sheet, can significantly improve the power performance of the battery cell.

[0041] In some embodiments, 0.85≤a≤0.95. The above-mentioned positive electrode active material system, in combination with the above-mentioned electrolyte and negative electrode plate, can significantly improve the power performance of the battery cell.

[0042] In some embodiments, the positive electrode active material includes at least one of single crystal particles and polycrystalline particles. The positive electrode active material system combined with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0043] In some embodiments, the positive electrode active material includes single crystal particles and polycrystalline particles. The positive electrode active material system combined with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0044] In a second aspect, the present application further proposes a battery, comprising a battery cell as described in any embodiment of the first aspect of the present application.

[0045] In a third aspect, the present application further proposes an electrical device, comprising a battery as described in any embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0047] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0048] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0049] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0050] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0051] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0052] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0053] The drawings are not necessarily drawn to scale.

[0054] The following are the descriptions of the reference numerals:

[0055] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0056] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0057] 53. Cover plate;

[0058] 6. Electrical equipment. DETAILED DESCRIPTION

[0059] Hereinafter, the battery cells, batteries and electrical devices of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0060] "Scope" disclosed in the present application is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0061] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0062] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0063] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0064] The discharge of a lithium-ion battery is the process in which lithium ions are released from the negative electrode active material and embedded in the positive electrode active material through the electrolyte. In the battery field, the industry often uses the "state of charge (SOC)" to reflect the remaining capacity of the battery after discharge. The value is defined as the percentage of the remaining capacity to the battery capacity, ranging from 0 to 100%. When "SOC = 0", it means that the battery is fully discharged, and when "SOC = 100%", it means that the battery is fully charged.

[0065] The lithium-ion battery discharge process has the problem of insufficient "discharge power" in the later stage of discharge. For example, when the battery is discharged to the state of charge (SOC) ≤ 10%, and continues to discharge to 0%, the discharge power performance is lower than the previous discharge, reducing the power performance of the battery during the entire discharge process.

[0066] In view of the above problems, the present application proposes a battery cell. The battery cell includes a negative electrode plate that is beneficial to improving the battery's later discharge power, and based on the negative electrode plate and an electrolyte that is beneficial to improving the battery's later discharge power, it can further include an adaptive separator and a positive electrode plate. The power performance of the battery in the later discharge period (especially the discharge process from SOC 10% to 0%) is significantly improved.

[0067] Battery Cell

[0068] The first aspect of the embodiment of the present application provides a battery cell, which includes a positive electrode plate, a separator, a negative electrode plate and an electrolyte. The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material; the electrolyte includes a lithium salt, the lithium salt includes lithium hexafluorophosphate, and the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte is 15% to 20%; the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and containing a negative electrode active material, the negative electrode active material also includes a carbon-based material and a silicon-carbon composite, and the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than or equal to 0.3% and less than or equal to 10.0%.

[0069] The negative electrode active material of the battery cell includes a carbon-based material that provides the carbon element and a silicon-carbon composite that provides the silicon element.

[0070] The carbon-based material providing the carbon element is mainly composed of carbon element, and may also contain silicon element, or may only contain carbon element; the silicon-carbon composite providing the silicon element may contain silicon element, may also contain carbon element, or may only contain silicon element. The negative electrode active material includes both the carbon-based material and the silicon-carbon composite, and the mass content of silicon element in the silicon-carbon composite relative to the total mass of the negative electrode active material is not less than 0.3%, taking into account the following reasons: Compared with the carbon-based material, the silicon-carbon composite has a higher lithium deintercalation voltage platform due to the presence of silicon element, so even at low SOC (for example, SOC ≤ 10%), the silicon-carbon composite can continue to participate in discharge, so as to make up for the deficiency that the carbon-based material is difficult / impossible to continue to discharge at low SOC, improve the DC internal resistance DCR of the battery during the discharge process, and then improve the power performance of the battery during the discharge process.

[0071] In the battery cell of the present application, the negative electrode active material is mainly carbon-based material, with a small amount of silicon-carbon composite added, that is, the mass content of silicon in the negative electrode active material is less than the mass content of carbon, and the mass content of silicon in the silicon-carbon composite relative to the total mass of the negative electrode active material is less than or equal to 10.0%, considering the following reasons:

[0072] Although the lithium deintercalation potential of silicon-carbon composites is higher than that of carbon-based materials, their volume expansion or contraction during the charge and discharge process is relatively large, which may cause structural collapse, cracking and pulverization of the negative electrode active material, and then trigger undesirable side reactions inside the battery. However, since the silicon-carbon composite contains carbon elements, the carbon element can effectively alleviate the volume expansion of silicon. Therefore, in this application, the upper limit of the mass content of silicon elements in the silicon-carbon composite can be slightly higher than the mass content of silicon elements in silicon oxide, which can be as high as 10%. Excessive content may not be conducive to improving DCR. Therefore, under the same other conditions, the battery power performance corresponding to the negative electrode active material of the silicon-carbon composite exceeding 10.0% is not as good as that of the battery with lower silicon content.

[0073] In order to further improve the problem of cracking and pulverization of the silicon-carbon composite, the battery monomer of the embodiment of the present application is used in combination with an electrolyte with a high content of lithium hexafluorophosphate LiPF6, and the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte is more than 15%.

[0074] Electrolytes with a high content of lithium hexafluorophosphate LiPF6 can effectively alleviate the problem of cracking and pulverizing of silicon-carbon composites. The possible reasons are: lithium hexafluorophosphate participates in the formation of the solid electrolyte interface (Solid Electrolyte Interphase, SEI) membrane component on the surface of the negative electrode active material. Lithium hexafluorophosphate with a high fluorine atom ratio can optimize the SEI membrane component, and lithium hexafluorophosphate with a high mass content has a more significant improvement effect on the SEI membrane component, which increases the proportion of fluorine lithium compounds (such as lithium fluoride) in the SEI membrane. This SEI membrane with a high proportion of fluorine lithium compounds can, on the one hand, alleviate the problem of cracking and pulverizing of silicon-carbon composites and improve the overall structural stability of negative electrode active materials. On the other hand, it can delay the side reactions on the surface of the electrolyte and the negative electrode active material, thereby improving the discharge stability of the silicon-carbon composite in the later stage of discharge and further improving the power performance of the battery.

[0075] In addition, at the end of the discharge of the battery cell at low SOC, the lithium ion concentration in the negative electrode active material is low, and it is relatively difficult for lithium ions to escape from the negative electrode active material, which reduces the concentration difference of lithium salts in the electrolyte system, increases the internal resistance of the battery cell, and further reduces the discharge power. However, since the electrolyte in the embodiment of the present application includes a high content of lithium hexafluorophosphate, it can contribute more lithium ions to the battery system, increase the lithium ion concentration in the electrolyte, effectively reduce the concentration polarization of lithium salts, and promote the migration of lithium ions from the negative electrode plate to the positive electrode plate, which can further improve the power performance of the battery cell.

[0076] However, when the mass content of lithium hexafluorophosphate in the electrolyte is greater than 20%, the viscosity of the electrolyte will be significantly increased, which is not conducive to the migration of lithium ions from the bulk phase of the negative electrode active material to the surface, and slows down the rate of lithium ions migrating from the negative electrode surface to the positive electrode surface. It is not conducive to the migration of lithium ions from the surface of the negative electrode active material to the bulk phase of the negative electrode active material. Therefore, even if the negative electrode active material contains silicon material with a higher lithium deintercalation voltage platform, without a suitable electrolyte system, the internal resistance of the battery at the end of discharge will increase, which is not conducive to the discharge power performance.

[0077] In summary, the mass content of lithium hexafluorophosphate in the electrolyte of the battery cell in the embodiment of the present application is 15% to 20%, combined with 0.3% to 10.0% silicon in the negative electrode active material, and the combined synergistic effect of the electrolyte and the negative electrode is utilized to improve the power performance of the battery at the end of discharge.

[0078] Exemplarily, the mass content of silicon in the silicon-carbon composite relative to the total mass of the negative electrode active material is 0.3% to 10.0%, and optionally 4.0% to 7.0%. For example, 0.3%, 0.4%, 0.5%, 0.6%, 0.64%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.27%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.91%, 2.0%, 2.1%, 2.2%, 2.23%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.86%, 2.9%, 3%, 3.1%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range consisting of any two of the above values.

[0079] In some embodiments, the mass content of silicon in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than or equal to 4.0% and less than or equal to 7.0%. The silicon-carbon composite within the above range can further improve the energy density of the battery cell, and because the carbon element in the silicon-carbon composite can alleviate the expansion of the silicon element, the expansion of the silicon-carbon composite will not be too large. It can significantly reduce the internal resistance of the battery at the end of discharge and improve the discharge power performance in combination with the above electrolyte system.

[0080] For example, the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte can be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 17.8%, 18%, 18.2%, 18.5%, 19%, 19.5%, 20%, or a range consisting of any two of the above values. The mass content of the silicon-carbon composite in the corresponding negative electrode active material relative to the total mass of the negative electrode active material is 0.5% to 10%.

[0081] As mentioned above, silicon can come from a silicon-carbon composite, where the silicon-carbon composite can refer to the form of silicon in the negative electrode of the battery after formation. The silicon-carbon composite can also be a silicon-carbon composite generated by certain chemical reactions between silicon and carbon in a battery cell. The silicon-carbon composite can also be formed by a physical mixture of silicon and carbon. For example, the carbon includes a porous skeleton, and the silicon is located in the pores of the porous skeleton or on the surface of the porous skeleton. The silicon-carbon composite can also be a carbon layer coated on the surface of the silicon.

[0082] In some embodiments, the negative electrode active material may also include other active materials containing silicon, such as silicon element in the form of silicon element, silicon oxide SiO xAt least one of the following forms (0<x≤2) exists in the negative electrode film layer. Here, silicon single substance, silicon-carbon composite, silicon oxide SiO x (0<x≤2) can refer to silicon-based materials or the existence form of silicon in the negative electrode of the battery after formation. The silicon oxide SiO x , 0<x≤2 is because the combination of silicon atoms and oxygen atoms in the negative electrode film layer is diverse, which can be SiO, SiO 1.2 , or SiO2 and at least one of other possible silicon oxides.

[0083] The carbon element is mainly a constituent element of the carbon-based material. In some embodiments, the carbon-based material may include at least one of artificial graphite and natural graphite.

[0084] Optionally, the carbon-based material may include artificial graphite, which, when combined with the above electrolyte system and the silicon-carbon composite, can reduce DCR and increase power.

[0085] In some embodiments, based on the total mass of the negative electrode active material, the ratio of the mass content of the silicon-carbon composite to the mass content of the artificial graphite is (0.4:99.6) to (14.5:85.5).

[0086] When the negative electrode active material meets the above-mentioned content ratio of the silicon-carbon composite and the artificial graphite, the discharge power of the battery at a low SOC can be further improved.

[0087] Illustratively, the ratio of the mass content of the silicon-carbon composite to the mass content of the artificial graphite can be 0.4:99.6, 0.5:99.5, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, 4.5:95.5, 5:95, 6.5:93.5, 7:93, 7.5:92.5, 8:92, 8.5:91.5, 9:91, 9.5:90.5, 10:90, 11:89, 12:88, 13:87, 14:86, 14.5:85.5 or a range consisting of any two of the above values.

[0088] In some embodiments, the mass content of the silicon-carbon composite is 0.4% to 14.5%, and can be 5.75% to 10%, for example, 0.4%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 5.5%, 5.75%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 14.5% or a range consisting of any two of the above values. When the mass content of the silicon-carbon composite meets the above content range, the cycle performance of the battery can be improved.

[0089] In some embodiments, the mass content of artificial graphite can be 85.5% to 99.6%, optionally 90% to 94.25%, for example, 85.5%, 90%, 91%, 92%, 93%, 94%, 95%, 95.1%, 95.2%, 95.3%, 95.4%, 95.5%, 95.6%, 95.7%, 95.8%, 95.9%, 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6 %, 96.7%, 96.8%, 96.9%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.8%, 98.9%, 99%, 99.5%, 99.6% or a range consisting of any two of the above values. When the mass content of artificial graphite meets the above content range, the cycle performance of the battery can be improved.

[0090] Optionally, the carbon-based material may include natural graphite. Natural graphite generally has a smaller particle size and can deintercalate lithium ions faster. The surface of natural graphite usually contains amorphous carbon. The presence of amorphous carbon can reduce DCR and increase power.

[0091] The qualitative and quantitative properties of each substance or element in this application can be detected by appropriate equipment and methods known to those skilled in the art. The relevant detection methods can refer to domestic and foreign detection standards, domestic and foreign enterprise standards, etc., and those skilled in the art can also adaptively change certain detection steps / instrument parameters, etc. from the perspective of detection accuracy to obtain more accurate detection results. One detection method can be used for qualitative or quantitative determination, or several detection methods can be used in combination for qualitative or quantitative determination.

[0092] For example, taking the detection of silicon elements in negative electrode active materials as an example, qualitative and quantitative analysis can be carried out by referring to JY / T015-1996 "General Rules for Inductively Coupled Plasma Atomic Emission Spectrometry", or further referring to GB-T17359-2012 standard to analyze the surface elements of the negative electrode sheet or the cross-section elements after ion polishing.

[0093] For example, the graphite material in this application can be combined with JIS / K0131-1996 X-ray diffraction analysis method general rules to perform X-ray powder diffraction test on the negative electrode sheet or negative electrode active material and conduct qualitative analysis. x (0<x≤2) can also be tested and qualitatively analyzed by the above-mentioned X-ray powder diffraction.

[0094] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode active material is greater than or equal to 85% and less than 100%. For example, the mass content of the negative electrode active material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or a range consisting of any two of the above values.

[0095] In some embodiments, the thickness of the single-sided negative electrode film layer is 65 μm to 90 μm. The thickness of the negative electrode film layer is the thickness of the single-sided negative electrode film layer. For example, negative electrode film layers are provided on both sides of the negative electrode current collector, and the thickness of the negative electrode film layer on one side of the negative electrode current collector is the thickness of the single side of the negative electrode film layer; or a negative electrode film layer is provided on one side of the two sides of the negative electrode current collector, and the thickness of the negative electrode film layer on that side is the thickness of the single-sided negative electrode film layer. When the thickness of the negative electrode film layer is within the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the separator can be basically consistent, reducing the risk of deteriorating concentration polarization, which is conducive to improving discharge performance.

[0096] Exemplarily, the thickness of the negative electrode film layer can be 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 79μm, 80μm, 81μm, 82μm, 83μm, 84μm, 85μm, 86μm, 87μm, 88μm, 89μm, 90μm or a range consisting of any two of the above values.

[0097] In the embodiments of the present application, the thickness of the negative electrode film layer has a well-known meaning in the art, and can be detected by using well-known equipment and methods in the art. The relevant detection methods can refer to domestic and foreign detection standards, domestic and foreign enterprise standards, etc., and those skilled in the art can also adaptively change certain detection steps / instrument parameters, etc. from the perspective of detection accuracy to obtain more accurate detection results. One detection method can be used for qualitative or quantitative determination, or several detection methods can be used in combination for qualitative or quantitative determination. For example, according to GB / T 17359-2012 "Quantitative Analysis by Microbeam Analysis Spectroscopy", the thickness of the negative electrode film layer can be obtained by using a negative electrode sheet that does not contain electrolyte as a sample for ion polishing cross-section elemental analysis. For another example, the average value is obtained by measuring multiple times with a micrometer: take a negative electrode sheet that does not contain electrolyte (a negative electrode sheet coated on both sides with a negative electrode film layer), first use a micrometer to test the thickness of any 5 sites on the negative electrode sheet, and get the average value H1, wipe the negative electrode film layer clean, then test the thickness of any 5 sites of the remaining current collector, and get the average value H2, then the thickness of the single-layer negative electrode film layer is (H2-H1) / 2.

[0098] In some embodiments, the compaction density PD of the negative electrode film layer is 1.3 g / cm 3 Up to 1.7g / cm 3 The compaction density of the negative electrode film layer is within this range, so that the negative electrode sheet has good dynamic performance and cycle performance.

[0099] For example, the compaction density PD of the negative electrode film layer may be 1.3 g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 Or a range consisting of any two of the above values.

[0100] Surface density = single-sided negative electrode film weight / single-sided negative electrode film area, where since the negative electrode current collector has negative electrode film on both sides, single-sided negative electrode film weight = (pole piece average weight - current collector average weight) / 2. Compacted density = surface density / average thickness of negative electrode film, where since the negative electrode current collector has negative electrode film on both sides, average thickness of negative electrode film = (pole piece average thickness - current collector average thickness) / 2.

[0101] The "average" here can be the average value after 5 parallel tests.

[0102] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application embodiment has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode conductive agent is ≤5%.

[0103] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include styrene-butadiene rubber SBR, water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS, polyacrylamide PAM, polyvinyl alcohol PVA, sodium alginate SA and carboxymethyl chitosan CMCS. At least one of. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode binder is ≤5%.

[0104] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include thickeners, such as sodium carboxymethyl cellulose CMC-Na, PTC thermistor materials, etc. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the other additives is ≤2%.

[0105] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material in the metal material layer may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0106] In some embodiments, the thickness of the negative electrode current collector is less than or equal to 6 μm; a thin current collector of 4.5 μm to 6 μm may be selected, for example, a thin metal current collector.

[0107] The negative electrode current collector of the battery cell of the present application can be selected as a thin current collector of 4.5μm to 6μm, so that the heat dissipation channel of the battery cell is weakened; under the low SOC discharge state, part of the heat can be retained in the battery, further increasing the beneficial effect of the low-silicon negative electrode plate with a high-content lithium hexafluorophosphate electrolyte system on reducing the DCR growth at the end of discharge (under low SOC), thereby improving the discharge power under low SOC.

[0108] Illustratively, the thickness of the negative electrode collector can be 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6 μm, or a range consisting of any two of the above values.

[0109] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0110] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the embodiment of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the embodiment of the present application further includes a protective layer covering the surface of the negative electrode film layer.

[0111] In some embodiments, the electrolyte further includes an organic solvent.

[0112] In some embodiments, the organic solvent may include cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate is (0.60 to 2.50):1, optionally (1.00 to 1.65):1 based on the total mass of the electrolyte.

[0113] The possible beneficial effects are speculated as follows: when the ratio of the mass content of cyclic carbonate to the mass content of lithium hexafluorophosphate is within the above range, it is beneficial to fully dissociate more lithium ions from the lithium hexafluorophosphate, so that even at the end of discharge at a low SOC, the electrolyte system can contain more lithium ions, and the lithium ions can be continuously dissociated as the battery reaction proceeds, so as to improve the power performance of the battery.

[0114] Illustratively, the ratio of the mass content of cyclic carbonate to the mass content of lithium hexafluorophosphate can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.15:1, 1.2:1, 1.3:1, 1.35:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1 or a range consisting of any two of the above values.

[0115] In some embodiments, the mass content of the cyclic carbonate in the electrolyte is 10% to 45%, and further optionally 20% to 30%. The cyclic carbonate has a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode active material, which is beneficial to the power performance of the battery at the end of discharge.

[0116] Illustratively, the mass content of cyclic carbonate can be 10%, 10.92%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 20.93%, 21%, 22%, 23%, 23.66%, 24%, 25%, 26%, 27%, 28%, 29%, 29.12%, 30%, 30.03%, 31%, 32%, 33%, 34%, 35%, 36%, 36.4%, 37%, 38%, 39%, 40%, 40.4%, 41%, 42%, 43%, 44%, 45% or a range consisting of any two of the above values.

[0117] In some embodiments, the cyclic carbonate may include at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.

[0118] In some embodiments, the organic solvent may include a linear carbonate, and based on the total mass of the electrolyte, the ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate is (0.9 to 6): 1; optionally (1.5 to 2.65): 1. When the mass content ratio of the linear carbonate to the cyclic carbonate meets the above range, it is possible to improve the viscosity and ionic conductivity of the electrolyte and enhance the kinetic properties of lithium ions.

[0119] For example, the ratio of the mass content of linear carbonate to the mass content of cyclic carbonate can be 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5.0:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1, 5.95:1, 6:1 The range formed by any two of the above values.

[0120] In some embodiments, the mass content of the linear carbonate is 35% to 65%, and further optionally 50% to 60%. The viscosity of the linear carbonate is relatively low, which helps to fully dissolve the high content of lithium hexafluorophosphate and facilitates the rapid migration of lithium ions ionized from the lithium hexafluorophosphate between the positive and negative electrodes. At the same time, the combination of the linear carbonate and the cyclic carbonate also helps to increase the electrochemical stability of the electrolyte system and effectively reduce the side reactions of the electrolyte.

[0121] Illustratively, the mass content of linear carbonate can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 50.4%, 51%, 52%, 52.5%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65% or a range consisting of any two of the above values.

[0122] In some embodiments, the linear carbonate includes at least one of ethyl methyl carbonate EMC, diethyl carbonate DEC, and dimethyl carbonate DMC.

[0123] In some embodiments, the electrolyte may further include additives.

[0124] In some embodiments, the additive may include a fluorinated cyclic carbonate.

[0125] In some embodiments, the fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, and trifluoropropylene carbonate TFPC; alternatively, the fluorinated cyclic carbonate includes monofluoroethylene carbonate FEC. FEC contains relatively fewer fluorine atoms, has stronger polarity, and fluorine is easier to be released to participate in the film-forming reaction of the SEI film.

[0126] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte to the mass content of the silicon element is (0.01 to 9.5):1, and can be optionally (0.01 to 0.15):1.

[0127] Exemplarily, the ratio of the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte to the mass content of the silicon element can be 0.01:1, 0.02:1, 0.03:1, 0.035:1, 0.04:1, 0.05:1, 0.055:1, 0.06:1, 0.07:1, 0.08:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.05:1, 1.1:1, 1.2:1, 1.3:1, 1.35:1, 1.4:1, 1.5:1 .5:1, 1.57:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.36:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 4.7:1, 4.71:1, 4.8:1, 5:1, 5.5:1, 5.8:1, 6:1, 6.5:1, 7:1, 7.5:1, 7.8:1, 8:1, 8.5:1, 9:1, 9.1:1, 9.2:1, 9.3:1, 9.4:1, 9.43:1, 9.5:1, or a range consisting of any two of the above values.

[0128] Fluorinated cyclic carbonates can participate in the formation of SEI film on the surface of negative electrode active materials, improve film composition and characteristics, and effectively protect negative electrode active materials: especially when the negative electrode contains silicon, due to the expansion characteristics of silicon, it is more necessary to optimize the film composition of SEI film formation. The film composition optimization is regulated by regulating the relative proportion of film-forming additives in the electrolyte. The film formed by the participation of fluorinated cyclic carbonates can improve the flexibility of the SEI film and improve the structural collapse caused by the release of a large number of lithium ions in a short period of time at the end of discharge; and fluorinated cyclic carbonates have a certain desolvation ability, which is conducive to the migration of lithium ions, and can improve the DCR at low SOC and increase the discharge power. After investigation, it was found that when the ratio of the silicon content in the negative electrode active material to the FEC content in the electrolyte meets (0.01 to 9.5): 1, the rate performance of the battery at the end of discharge is significantly improved. Since the carbon element in the silicon-carbon composite can effectively alleviate the volume change of the silicon element, the relatively low content of the fluorinated cyclic carbonate can also significantly improve the discharge power performance of the battery cell. Optionally, the ratio of the silicon content in the negative electrode active material to the FEC content in the electrolyte satisfies (0.01 to 0.15):1.

[0129] In some embodiments, the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte may be 0.05% to 5.8%, and optionally 0.1% to 1.0%.

[0130] For example, the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.95%, 0.98%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.91, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.82%, 3.9%, 4%, 4.1%, 4.5%, 5%, 5.2%, 5.5%, 5.7%, 5.73%, 5.8% or a range consisting of any two of the above values.

[0131] In some embodiments, the additive may further include at least one of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO 3 F.

[0132] In some embodiments, based on the total mass of the electrolyte, the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC and the mass content of lithium fluorosulfonate LiSO3F is (0.050 to 0.300): (0.100 to 0.500): (0.001 to 0.300). When the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC and the mass content of lithium fluorosulfonate LiSO3F is within the above range, the above components can basically participate in the formation of SEI film on the surface of the negative electrode active material, so that the SEI film can effectively alleviate the expansion of the silicon-carbon composite.

[0133] In some embodiments, the mass content of 1,3-propane sultone PS is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or a range consisting of any two of the above values.

[0134] In some embodiments, the mass content of vinylene carbonate VC is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or a range consisting of any two of the above values.

[0135] In some embodiments, the mass content of lithium fluorosulfonate LiSO3F is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or a range consisting of any two of the above values.

[0136] After lithium salts are dissolved in organic solvents, they can release a large amount of active lithium ions to participate in charging and discharging. Some lithium salts can also optimize the structure of the SEI film, improve the reaction activity of the electrolyte, reduce side reactions, and thus increase the discharge power of the battery.

[0137] In some embodiments, based on the total mass of the electrolyte, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.005 to 0.30):1, optionally (0.005 to 0.03):1.

[0138] Fluorinated cyclic carbonates can form organic matter on the surface of the silicon-carbon composite, improving the flexibility of the SEI film; lithium salts can participate in the formation of the SEI film, so that the SEI film contains inorganic components, which is beneficial to improving the ion conductivity and electronic conductivity of the SEI film, and can improve the overall ion conductivity and electronic conductivity of the negative electrode plate; when the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is within the above range, while taking into account the improvement of the flexibility, ion conductivity and electronic conductivity of the SEI film, it can also reduce the DCR, thereby improving the discharge power of the battery.

[0139] For example, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt can be 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.010:1, 0.012:1, 0.014:1, 0.016:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.010:1, 0.012:1, 0.014:1, 0.016:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.011:1 .10:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1, 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, 0.30:1 or a range consisting of any two of the above values.

[0140] In some embodiments, the lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate. The fluorine-containing inorganic phosphate and the fluorine-containing inorganic borate can participate in the formation of inorganic components in the SEI film, which is beneficial to improving the ion-conducting and electron-conducting properties of the SEI film, and the interface ion impedance of the formed SEI film is low, which is beneficial to the transmission of lithium ions and can improve the DCR at low SOC.

[0141] In some embodiments, the fluorine-containing inorganic phosphate includes at least one of lithium monofluorophosphate Li2PO3F and lithium difluorophosphate LiPO2F2; alternatively, the fluorine-containing inorganic phosphate includes lithium difluorophosphate LiPO2F2.

[0142] In some embodiments, the fluorine-containing inorganic borate comprises at least one of lithium tetrafluoroborate LiBF4 and lithium difluorooxalatoborate LiDFOB. Alternatively, the fluorine-containing borate comprises lithium tetrafluoroborate LiBF4.

[0143] In some embodiments, based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic phosphate or fluorine-containing inorganic borate is 0.05% to 0.50%, and optionally 0.10% to 0.30%.

[0144] Illustratively, the mass content of the fluorine-containing inorganic phosphate or fluorine-containing inorganic borate can be 0.05%, 0.06%, 0.08%, 0.1%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5% or a range consisting of any two of the above values.

[0145] Illustratively, the lithium salt includes lithium difluorophosphate LiPO2F2 and lithium tetrafluoroborate LiBF4.

[0146] Optionally, based on the total mass of the electrolyte, the mass content of lithium difluorophosphate LiPO2F2 can be 0.05% to 0.5%, optionally 0.10% to 0.30%. For example, the mass content of lithium difluorophosphate LiPO2F2 can be 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or a range consisting of any two of the above values.

[0147] Optionally, based on the total mass of the electrolyte, the mass content of lithium tetrafluoroborate LiBF4 can be 0.1% to 0.3%. For example, the mass content of lithium tetrafluoroborate LiBF4 can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or a range consisting of any two of the above values.

[0148] Optionally, based on the total mass of the electrolyte, the mass content of lithium difluorooxalatoborate LiDFOB may be 0.01% to 0.1%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1% or a range consisting of any two of the above values.

[0149] The qualitative and quantitative properties of each substance or element in this application can be detected by appropriate equipment and methods known to those skilled in the art. The relevant detection methods can refer to domestic and foreign detection standards, domestic and foreign enterprise standards, etc., and those skilled in the art can also adaptively change certain detection steps / instrument parameters, etc. from the perspective of detection accuracy to obtain more accurate detection results. One detection method can be used for qualitative or quantitative determination, or several detection methods can be used in combination for qualitative or quantitative determination.

[0150] In the embodiments of the present application, the types and contents of the inorganic components / lithium salt concentrations in the electrolyte are well-known in the art, and can be detected by equipment and methods well-known in the art. For example, the inorganic components / lithium salt concentrations in the electrolyte can be qualitatively or quantitatively analyzed by ion chromatography analysis methods with reference to the standard JY / T020-1996 "General Rules for Ion Chromatography Analysis Methods". In the embodiments of the present application, a newly prepared electrolyte can be taken as a sample, or a battery that has been fully discharged (discharged to the lower limit cut-off voltage so that the battery is charged at about 0% SOC) can be reversely disassembled, and the free electrolyte obtained from the battery can be used as a sample, and the ion chromatography analysis method can be used for detection.

[0151] In the embodiments of the present application, the type and content of the organic components in the electrolyte are well-known in the art, and can be detected by using equipment and methods well-known in the art. For example, reference can be made to GB / T9722-2006 "General Rules for Gas Chromatography of Chemical Reagents" to perform qualitative and quantitative analysis of the organic components in the electrolyte by gas chromatography. In the embodiments of the present application, a newly prepared electrolyte can be taken as a sample, or a battery that has been fully discharged (discharged to the lower limit cut-off voltage so that the battery's charged state is about 0% SOC) can be reversely disassembled, and the free electrolyte obtained from the battery can be used as a sample, and the ion chromatography analysis method can be used for detection.

[0152] For another example, using liquid nuclear magnetic chromatography (NMR) to test the composition of an additive in an electrolyte, taking the detection of lithium difluorophosphate and lithium hexafluorophosphate as an example, in a nitrogen glove box, prepare a 7ml glass bottle, add 5ml of nuclear magnetic reagent premix to the glass bottle, and let it stand for 24 hours at room temperature of 20-25°C in a nitrogen atmosphere glove box, so that the electrolyte in the pole piece and the isolation membrane diffuses into the nuclear magnetic premix, thereby obtaining a nuclear magnetic test sample. The nuclear magnetic premix includes 100ml of deuterated acetonitrile and 3ml of trifluoromethylbenzene C7H5F3. The above nuclear magnetic reagent premix is ​​pre-dried with molecular sieve 4A in advance (100ml of nuclear magnetic reagent premix is ​​added with 15g of newly opened 4A molecular sieve at room temperature of 20-25°C and dried in a nitrogen glove box for more than 30 days). 19F NMR measurement (nuclear magnetic (NMR): Bruker Avance 400HD).

[0153] To identify and quantify individual species, the following settings were used in terms of flip angle and scanning time.

[0154] Fluorine spectrum test pulse sequence: 2gfhigqn.2;

[0155] Delay time: 1 second;

[0156] Number of scans: 16 times.

[0157] The relative contents of trifluoromethylbenzene and LiPF6 were calculated based on the signal peak integral intensity of the two substances in F-NMR. The calculation method is:

[0158] PF6 - Relative content = (I PF6 - ×M PF6 - / 6) / (I CF3ph ×M CF3ph / 3), where I is the corresponding NMR peak area, M is the corresponding relative molecular mass, and then the content of lithium hexafluorophosphate in the electrolyte is calculated based on the molar ratio of hexafluorophosphate to lithium ions.

[0159] Based on trifluoromethylbenzene and PO2F2 in F-NMR - The relative content of the two substances is calculated by the integrated intensity of the signal peaks. The calculation method is:

[0160] PO2F2 - Relative content = (I PO2F2- ×M PO2F2- / 2) / (I CF3ph ×M CF3ph / 3), where I is the corresponding NMR peak area, M is the corresponding relative molecular mass, and then the content of lithium difluorophosphate in the electrolyte is calculated based on the molar ratio of difluorophosphate to lithium ions.

[0161] In some embodiments, the various solutes or solvents in the electrolyte mentioned in the present application include substances actively added when preparing the electrolyte, and also include substances derived from certain substances already existing in the electrolyte during the preparation of the electrolyte or in the process of preparing a battery from the electrolyte or during the storage or use of a battery containing the electrolyte.

[0162] In some embodiments, the battery cell has a liquid retention coefficient of 1.0 g / Ah to 2.5 g / Ah, and optionally 1.0 g / Ah to 1.5 g / Ah.

[0163] The liquid retention coefficient of the battery cell can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of the battery cell is within the above range, the electrolyte can have a good infiltration effect on the positive electrode plate and the negative electrode plate; and there is a certain gap between the negative electrode plate and the isolation membrane, which can provide expansion space for the volume expansion of the silicon-carbon composite and reduce the risk of overall bulging of the battery.

[0164] Exemplarily, the liquid retention coefficient of the battery can be 1.0g / Ah, 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah, 1.6g / Ah, 1.7g / Ah, 1.8g / Ah, 1.9g / Ah, 2.0g / Ah, 2.1g / Ah, 2.2g / Ah, 2.3g / Ah, 2.4g / Ah, 2.5g / Ah or a range consisting of any two of the above values.

[0165] In the embodiment of the present application, the liquid retention coefficient of the battery cell is a well-known meaning in the art, and can be tested by using well-known equipment and methods in the art. For example, according to GB / T 31486-2015 "Electrical Performance Requirements and Test Methods for Power Batteries for Electric Vehicles", at 25°C, the lithium-ion battery is charged to 4.35V at 1C, and then discharged to 2.8V at 1C, and the released capacity C is used as the denominator; the lithium-ion battery is weighed as M0, and then the positive electrode sheet, negative electrode sheet, separator and electrolyte are disassembled, wherein the free electrolyte exists in the shell / bag, and all the above solid components are placed in a 60°C oven for more than 4 hours (including but not limited to the positive electrode sheet, negative electrode sheet, separator, and other mechanical parts of the disassembled battery cell that contribute to M0), and then all the components of the battery cell are weighed M1, wherein the weight difference between M0 and M1 is used as the numerator. The liquid retention coefficient is equal to the value obtained by dividing the capacity C by the weight difference between M0 and M1.

[0166] In some embodiments, the battery cell may further include a separator, and the separator may have a porosity of 30% to 40%.

[0167] Since the amount of lithium hexafluorophosphate added to the battery cell of the present application is relatively high, the overall viscosity of the electrolyte is relatively large; the porosity of the isolation membrane is relatively high, which is conducive to the penetration of the electrolyte with higher viscosity through the isolation membrane, allowing lithium ions to migrate smoothly.

[0168] Exemplarily, the porosity of the isolation membrane can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% or a range consisting of any two of the above values.

[0169] In the embodiment of the present application, the porosity refers to the percentage of the pore volume in the separator to the total volume of the separator. The porosity can be tested according to the standard GB / T 36363-2018 "Polyolefin separator for lithium ion batteries".

[0170] In some embodiments, the isolation film includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating includes a heat-resistant layer and an organic layer, the heat-resistant layer is located on the surface of the organic substrate, and the organic layer is disposed on the surface of the heat-resistant layer away from the organic substrate. The isolation film, in combination with the electrolyte and the negative electrode sheet, can significantly improve the power performance of the battery cell.

[0171] Optionally, the heat-resistant layer includes inorganic particles. The above-mentioned separator, together with the above-mentioned electrolyte and the negative electrode plate, can significantly improve the power performance of the battery cell.

[0172] Optionally, the organic layer includes one of a non-fluorinated polymer and a fluorinated polymer. Optionally, the organic layer includes a non-fluorinated polymer, for example, the non-fluorinated polymer includes polyacrylate. In this case, the organic layer is a polyacrylate layer. The above-mentioned isolation film, in combination with the above-mentioned electrolyte and the negative electrode plate, can significantly improve the power performance of the battery cell.

[0173] For example, the coating may include a ceramic layer and / or a polyacrylate layer. The coating may include only a ceramic layer, or only a polyacrylate layer, or both a ceramic layer and a polyacrylate layer.

[0174] Optionally, when the coating includes a ceramic layer and a polyacrylate layer, the polyacrylate layer can be disposed on at least one surface of the organic substrate, and the ceramic layer can be disposed on the surface of the polyacrylate layer facing away from the organic substrate; or, the ceramic layer can be disposed on at least one surface of the organic substrate, and the polyacrylate layer can be disposed on the surface of the ceramic layer facing away from the organic substrate.

[0175] The isolation membrane sets the polyacrylate layer on the outer surface of the isolation membrane, so that the outer surface of the isolation membrane has a certain flexibility, which can effectively alleviate the volume expansion or contraction of the silicon-carbon composite and improve the overall structural stability of the electrode assembly.

[0176] The material of the organic substrate is not particularly limited, and any known base film with good chemical stability and mechanical stability can be selected. For example, the organic substrate includes at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl fluoride, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The organic substrate can be selected from a single-layer film or a multi-layer composite film. When the organic substrate is a multi-layer composite film, the materials of each layer can be the same or different.

[0177] In some embodiments, the thickness of the organic substrate is from 6.6 μm to 7.6 μm.

[0178] When the thickness of the organic substrate is within the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the isolation membrane can be basically consistent, reducing the risk of deteriorating concentration polarization and helping to improve discharge performance.

[0179] Illustratively, the thickness of the organic substrate may be 6.6 μm, 6.7 μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm, 7.5 μm, 7.6 μm, or a range consisting of any two of the above values.

[0180] In some embodiments, the polyacrylate in the polyacrylate layer can be formed by polymerizing a polymer monomer, and the polymer monomer includes at least one of a first polymer monomer, a second polymer monomer, and a third polymer monomer. Optionally, the polymer monomer includes a first polymer monomer, a second polymer monomer, and a third polymer monomer. The polyacrylate is polymerized using the above three polymer monomers, so that the isolation film can obtain suitable adhesion with the pole piece, thereby improving the dynamic performance of the battery.

[0181] The first polymer monomer has at least one ester bond, and can be selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate or trimethylolpropane triacrylate, and can be further selected from one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate or trimethylolpropane triacrylate.

[0182] The second polymer monomer has at least one cyanide bond, and may be selected from one or more of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and may be further selected from one or more of acrylonitrile and methacrylonitrile.

[0183] The third polymer monomer has at least one amide bond, and may be one or more of acrylamide, N-hydroxymethyl acrylamide, and N-butoxymethyl acrylamide, and may be one or more of acrylamide and N-hydroxymethyl acrylamide.

[0184] In some embodiments, the weight ratio of the first polymer monomer, the second polymer monomer and the third polymer monomer in the above-mentioned polyacrylate is (45 to 70): (10 to 25): (10 to 35), for example, (50 to 70): (10 to 25): (10 to 35), (55 to 70): (10 to 25): (10 to 35), (60 to 70): (10 to 25): (10 to 35), (65 to 70): (10 to 25): (10 to 35), (45 to 70): (15 to 25): (10 to 35), (45 to 70): (20 to 25): (10 to 35), (45 to 70): (22 to 25): (10 to 35), (45 to 70): (10 to 25): (15 to 35), (45 to 70): (10 to 25): (20 to 35), (45 to 70): (10 to 25): (25 to 35), (45 to 70): (10 to 25): (30 to 35), (45 to 70): (10 to 25): (32 to 35), etc.

[0185] In some embodiments, the ceramic layer includes inorganic particles having heat resistance, and the inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or higher, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.

[0186] In some embodiments, inorganic particles having a dielectric constant of 5 or more may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-nTi n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT).

[0187] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass (0<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).

[0188] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0189] In some embodiments, the ceramic layer may further include a binder; optionally, the binder includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.

[0190] In some embodiments, the coating has a thickness of 1.5 μm to 2.5 μm.

[0191] The thickness of the coating is the thickness of the coating on one side, specifically including the total thickness of the ceramic layer and the polyacrylate layer. For example, if the organic substrate is provided with coatings on both sides, the thickness of the coating on one side of the organic substrate is the thickness of the coating on one side; or if the organic substrate is provided with coatings on one side, the thickness of the coating on that side is the thickness of the coating on the single side. When the thickness of the coating is within the above range, the transmission rate of lithium ions in the negative electrode plate and the transmission rate in the separator can be basically consistent, reducing the risk of deteriorating concentration polarization, which is conducive to improving discharge performance.

[0192] Illustratively, the thickness of the coating may be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, or a range consisting of any two of the above values.

[0193] In some embodiments, the ratio of the thickness of the ceramic layer to the thickness of the polyacrylate layer can be (0.5 to 2.0):1, for example 0.5:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, or a range consisting of any two of the above values.

[0194] In the embodiment of the present application, the meanings of the thickness of the organic substrate and the coating are well-known in the art, and can be detected by using well-known equipment and methods in the art, for example, the test can be performed by using an ion cross-section polisher in combination with a scanning electron microscope. As an example, the following steps can be followed: first, the isolation film is cut into a sample to be tested of a certain size (for example, 6 mm×6 mm), the sample to be tested is clamped with two conductive and thermally conductive sheets (such as copper foil), the sample to be tested and the sheet are glued and fixed with glue (such as double-sided tape), a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors, and the sample is glued to a sample table with conductive glue, and the sample slightly protrudes from the edge of the sample table. Then put the sample stage into the sample holder and lock it, turn on the power of the argon ion cross-section polisher and evacuate it (for example, 10Pa-4Pa), set the argon gas flow rate (for example, 0.15MPa) and voltage (for example, 8KV) and polishing time (for example, 2 hours), adjust the sample stage to the swing mode and start polishing. After polishing, use a scanning electron microscope (for example, ZEISS Sigma 300) to obtain an ion polishing cross-sectional morphology (CP) image of the sample to be tested, and measure the thickness of the coating and the thickness of the organic substrate.

[0195] In some embodiments, the battery cell further includes a positive electrode tab.

[0196] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0197] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material can adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a layered structure positive electrode active material (such as lithium nickel cobalt manganese oxide, lithium nickel oxide / sodium, lithium cobalt oxide / sodium, lithium manganese oxide / sodium, lithium / sodium rich layered and rock salt phase layered materials), an olivine type phosphate active material, a spinel structured positive electrode active material (such as spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium-rich spinel lithium manganese oxide, and lithium nickel manganese oxide, etc.).

[0198] In some embodiments, the positive electrode active material includes a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) Y zCompounds, wherein 0<d≤2.1, 0.6<a<1, 0<b<1, 0<c<1, and 0.6<a+b+c<1, 1.8≤z≤3.5, M element includes at least one element of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce; Y element includes at least one element of O and F. The above-mentioned positive electrode active material system, in combination with the above-mentioned electrolyte and negative electrode sheet, can significantly improve the power performance of the battery cell.

[0199] In addition to lithium, the positive electrode active materials also include nickel, cobalt, manganese and M elements. Nickel can increase the gram capacity of the positive electrode active materials, cobalt can stabilize the crystal structure of the positive electrode active materials, manganese can improve the overall structural stability of the positive electrode active materials, and M can improve the crystal structure stability of the positive electrode active materials.

[0200] In some embodiments, d can be 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72 , 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1 or a range consisting of any two of the above values.

[0201] In some embodiments, 0.85≤a≤0.95.

[0202] a can be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or a range consisting of any two of the above values. The above-mentioned positive electrode active material system, in combination with the above-mentioned electrolyte and negative electrode sheet, can significantly improve the power performance of the battery cell.

[0203] In some embodiments, b can be 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or a range consisting of any two of the above values.

[0204] In some embodiments, c can be 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or a range consisting of any two of the above values.

[0205] In some embodiments, a+b+c can be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above values.

[0206] In some embodiments, z can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5 or a range consisting of any two of the above values.

[0207] The battery is accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.

[0208] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.

[0209] In some embodiments, the M element includes at least one of titanium Ti and zirconium Zr; alternatively, M includes Ti and Zr elements. Both Ti and Zr can improve cycle performance.

[0210] In some embodiments, the total mass content of Ti and Zr elements is 1600 ppm to 3150 ppm based on the total mass of the positive electrode active material. When the addition amount of Ti and Zr elements is within the above range, the crystal structure of the positive electrode active material can be further improved, and the cycle performance can be improved.

[0211] The total mass content of Ti and Zr elements refers to the ratio of the total mass of Ti and Zr elements to the total mass of the positive electrode active material.

[0212] Illustratively, the total mass content of Ti and Zr elements can be 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3150ppm or a range consisting of any two of the above values.

[0213] In some embodiments, based on the total mass of the positive electrode active material, the mass content of the Ti element is 100 ppm to 600 ppm, for example, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm or a range consisting of any two of the above values.

[0214] In some embodiments, based on the total mass of the positive electrode active material, the mass content of the Zr element is 500ppm to 2550ppm; it can be optionally 1500ppm to 2550ppm, for example, it can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2550ppm or a range composed of any two of the above values.

[0215] In some embodiments, at least one of lithium difluorooxalatoborate LiDFOB and lithium tetrafluoroborate LiBF4 in the electrolyte can provide fluoride ions and boron ions. In the later stage of battery cycle, metal ions such as Ti and Zr ions in the positive electrode active material have the risk of dissolving into the electrolyte and migrating to the surface of the negative electrode plate; fluoride ions and boron ions can have a strong binding ability with the above metal ions, reduce the risk of metal ions migrating to the surface of the negative electrode plate, and improve the cycle performance of the battery; and can also compensate for the power deterioration caused by Ti and Zr ions.

[0216] In some embodiments, the positive electrode active material includes at least one of single crystal particles and polycrystalline particles. The positive electrode active material system combined with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0217] In some embodiments, the positive electrode active material includes a single crystal particle, the single crystal particle includes an inner region and an outer region, the outer region is a region extending 500 nm straight toward the interior of the single crystal material from any point on the outer surface of the single crystal particle; the M element includes aluminum Al element, and the aluminum Al element is distributed at least in the outer region.

[0218] The inner region of the single crystal particle can be understood as the core of the single crystal particle, and the outer region is covered outside the inner region; there may be no obvious boundary between the outer region and the inner region, and the outer region and the inner region can be considered as two artificially defined regions. The outer region is the region extending 500nm from any point on the outer surface of the single crystal particle toward the inside of the single crystal particle, and the extension path is a straight line path. The outer region can be understood as an annular structure, and the radial spacing of the annular structure is less than or equal to 500nm.

[0219] In some embodiments, the positive electrode active material includes single crystal particles and polycrystalline particles. The positive electrode active material system combined with the electrolyte and the negative electrode plate can significantly improve the power performance of the battery cell.

[0220] The aluminum Al element is at least distributed in the outer region, which helps to form aluminum oxide Al2O3 in the positive electrode active material, can passivate the side reaction between the positive electrode active material and the electrolyte, further improve the structural stability of the positive electrode active material, and improve the cycle performance of the battery. Of course, in addition to being distributed in the outer region, the Al element can also be further distributed in the inner region.

[0221] In some embodiments, based on the total mass of the positive electrode active material, the mass content of the Al element is 500 ppm to 3000 ppm, optionally 1000 ppm to 2000 ppm.

[0222] Illustratively, the mass content of the Al element can be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm or a range consisting of any two of the above values.

[0223] In some embodiments, the combination of lithium difluorophosphate LiPO2F2 in the electrolyte and Al element in the positive electrode active material can improve the DCR on the surface of the positive electrode active material and enhance the interface power.

[0224] In some embodiments, the M element includes at least one of phosphorus P, sulfur S and boron B; optionally, the M element includes phosphorus P, sulfur S and boron B. Phosphorus P, sulfur S and boron B can improve the structural stability of the positive electrode active material and improve the cycle performance of the battery.

[0225] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of P, S and B elements is 0 to 800 ppm, optionally 10 ppm to 500 ppm, such as 0, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm or a range consisting of any two of the above values. When the total mass content of P, S and B elements is 0, it means that such elements are not added.

[0226] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of the P element is 10ppm to 500ppm, for example, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 80ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 600ppm, 700ppm, 800ppm or a range consisting of any two of the above values.

[0227] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of the S element is 10ppm to 500ppm, for example, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 80ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 600ppm, 700ppm, 800ppm or a range consisting of any two of the above values.

[0228] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of the B element is 10ppm to 500ppm, for example, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 80ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 600ppm, 700ppm, 800ppm or a range consisting of any two of the above values.

[0229] In some embodiments, the electrolyte additive may further include lithium fluorosulfonate; a low-impedance film component can be formed on the surface of the positive electrode active material; the combination of lithium fluorosulfonate and phosphorus P, sulfur S and boron B elements in the positive electrode active material can reduce the DCR on the surface of the positive electrode active material and improve the interface power.

[0230] In the embodiment of the present application, the content of the element in the positive electrode active material has a well-known meaning in the art, and can be detected by equipment and methods well-known in the art, for example, with reference to EPA6010D-2014, tested by inductively coupled plasma atomic emission spectrometry, and measured by plasma atomic emission (ICP-OES, instrument model: Thermo ICAP7400). First, weigh 0.4g of the positive electrode active material and add 10ml (50% concentration) of aqua regia thereto. Then place it on a plate at 180°C for 30min. After digestion on the plate, dilute to a volume of 100mL, and use the standard curve method for quantitative testing.

[0231] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application embodiment has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass content of the positive electrode conductive agent is ≤5%.

[0232] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application embodiment has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and at least one of fluorine-containing acrylic resins. In some embodiments, based on the total mass of the positive electrode film layer, the mass content of the positive electrode binder is ≤5%.

[0233] In some embodiments, the ratio of the compaction density of the positive electrode film layer to the compaction density of the negative electrode film layer is (2 to 2.5): 1. For example, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1 or a range consisting of any two of the above values.

[0234] In some embodiments, the compaction density PD of the positive electrode layer is 3 g / cm 3 Up to 3.5g / cm 3 For example, 3g / cm 3 、3.1g / cm 3 、3.2g / cm 3, 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 Or a range consisting of any two of the above values.

[0235] In the embodiments of the present application, the compaction density of the positive electrode active material layer has a well-known meaning in the art and can be tested by methods known in the art. For example, take a single-sided coated and cold-pressed positive electrode sheet (if it is a double-sided coated positive electrode sheet, the positive electrode film on one side can be wiped off first), punch it into small discs with an area of ​​S1, weigh it, and record it as M1. Then wipe off the positive electrode film of the weighed positive electrode sheet, weigh the weight of the positive electrode collector, and record it as M0. The surface density of the positive electrode active material layer = (the weight of the positive electrode sheet M1-the weight of the positive electrode collector M0) / S1, and the compaction density of the positive electrode active material layer = the surface density of the positive electrode active material layer / the thickness of the positive electrode active material layer.

[0236] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0237] In some embodiments, the thickness of the positive electrode current collector is less than or equal to 13 μm; optionally 8 μm to 13 μm, or optionally 10 μm to 13 μm.

[0238] The thickness of the positive electrode current collector is relatively thin, which can weaken the heat dissipation channel of the battery; under low SOC discharge state, some heat can be retained in the battery cell, which is beneficial to improve the DCR under low SOC, thereby improving the discharge power under low SOC.

[0239] Illustratively, the thickness of the positive electrode collector may be 8 μm, 8.2 μm, 8.5 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.5 μm, 9.6 μm, 9.8 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, or a range consisting of any two of the above values.

[0240] In the embodiment of the present application, the thickness of the positive electrode current collector has a well-known meaning in the art and can be detected by using equipment and methods well-known in the art. For example, the positive electrode plate is used as a sample, and then the positive electrode film layer on the surface of the positive electrode plate is washed away with an organic solvent such as alcohol, and the thickness of the positive electrode current collector is measured with a micrometer.

[0241] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0242] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly by a winding process and / or a lamination process; it can be understood that the electrode assembly can be a wound electrode assembly, or a laminated electrode assembly; optionally, the electrode assembly is a laminated electrode assembly, and the laminated electrode assembly makes the positive electrode sheet and the negative electrode sheet tighter, which can further improve the DCR.

[0243] In some embodiments, the battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0244] In some embodiments, the outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0245] The shape of the battery is not particularly limited in the present application, and it can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0246] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0247] The preparation method of the battery of the embodiment of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0248] In some embodiments of the embodiments of the present application, the batteries according to the embodiments of the present application can be assembled into a battery module. The number of batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0249] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0250] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0251] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0252] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0253] Electrical devices

[0254] The second aspect of the embodiments of the present application provides an electrical device, which includes at least one of the batteries, battery modules or battery packs of the embodiments of the present application. The battery, battery module or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0255] The electrical device can select batteries, battery modules or battery packs according to its usage requirements.

[0256] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.

[0257] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be thin and light, and a battery may be used as a power source.

[0258] Example

[0259] The following examples more specifically describe the contents disclosed in the embodiments of the present application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the disclosure of the embodiments of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0260] Example 1

[0261] 1. Preparation of positive electrode sheet

[0262] The positive electrode sheet includes a positive electrode collector and a positive electrode film layer. The positive electrode collector is an aluminum foil with a thickness of 10 μm. The positive electrode film layer includes a film layer formed by uniformly coating a positive electrode slurry (the solvent is N-methylpyrrolidone NMP) on the surface of the positive electrode collector aluminum foil, drying, and cold pressing. The positive electrode film layer includes a positive electrode active material, a conductive agent carbon black, and a binder polyvinylidene fluoride (PVDF) in a weight ratio of 97.5:1.4:1.1.

[0263] The positive electrode active material is a single crystal structure, which includes a molecular formula of Li d Nia Co b Mn c M (1-a-b-c) O z The compound, wherein the nickel-cobalt-manganese oxide matrix in the positive electrode active material includes a molecular formula of LiNi 0.70 Co 0.10 Mn 0.20 O2 compounds.

[0264] The M element includes 450 ppm of Ti element, 1700 ppm of Zr element, 1600 ppm of Al element and 120 ppm of (B, S and P) elements.

[0265] 2. Preparation of negative electrode sheet

[0266] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer. The negative electrode current collector is a copper foil with a thickness of 4.5 μm. The negative electrode film layer includes a film layer formed by uniformly coating a negative electrode slurry (the solvent is deionized water) on the surface of the negative electrode current collector copper foil, drying, and cold pressing. The negative electrode film layer includes a negative electrode active material, a binder styrene-butadiene rubber (SBR), a thickener sodium carboxymethyl cellulose (CMC-Na), and a conductive agent carbon black (Super P) in a weight ratio of 96.2:1.8:1.2:0.8.

[0267] The negative electrode active material includes 97% of artificial graphite and 3% of silicon oxide SiO, and the mass content of silicon element relative to the total mass of the negative electrode active material is 1.91%.

[0268] 3. Isolation film

[0269] The isolation membrane can be purchased directly from Ningde Zhuo Gao New Material Technology Co., Ltd. The porosity of the isolation membrane is 30%, and the isolation membrane includes an organic substrate (porous polypropylene PP (7μm)) and a coating, the coating includes a ceramic layer (1μm) and a polyacrylate layer (1μm), the ceramic layer is arranged on both surfaces of the organic substrate, the ceramic layer includes a film layer formed by dissolving a binder and inorganic aluminum oxide in N-methylpyrrolidone NMP and coating on the organic substrate, the polyacrylate layer is arranged on the surface of the ceramic layer away from the organic substrate, and the polyacrylate layer is a film layer formed by coating a substance containing polyacrylates on the surface of the ceramic layer.

[0270] 4. Preparation of electrolyte

[0271] The electrolyte includes an organic solvent, a lithium salt and an additive, wherein the organic solvent includes cyclic carbonates (EC, PC and BC, each component has a mass ratio of 1:1:1) and linear carbonates (EMC, DMC and DEC, each component has a mass ratio of 1:1:1); the additive includes a fluorinated cyclic carbonate FEC. The additive also includes at least one of PS, VC and LiSO3F, and the total content thereof is ≤2%.

[0272] 5. Preparation of batteries

[0273] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained, and the liquid retention coefficient of the lithium-ion battery is 2.0g / Ah.

[0274] Comparative Example 1

[0275] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the negative electrode active material of Comparative Example 1 is different. The negative electrode active material includes 94% artificial graphite and 6% silicon oxide SiO, and the mass content of silicon element is 3.82%.

[0276] Comparative Example 2 and Comparative Example 3

[0277] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the components of the electrolyte, especially the content of lithium hexafluorophosphate, were adjusted in Comparative Examples 2 and 3.

[0278] Comparative Example 4

[0279] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the negative electrode active material of Comparative Example 4 is different, and the negative electrode active material includes 100% artificial graphite.

[0280] Example 2-1 to Example 2-5

[0281] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that at least the composition of the negative electrode active material was adjusted in Examples 2-1 to 2-5.

[0282] Example 3-1 to Example 3-3

[0283] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that at least the composition of the negative electrode active material was adjusted in Examples 3-1 to 3-3.

[0284] Example 4 to Example 4-2

[0285] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that in Examples 4 to 4-2, at least the composition of the electrolyte, especially the mass content of lithium hexafluorophosphate, was adjusted.

[0286] Example 5-1 to Example 5-7

[0287] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that at least the composition of the electrolyte, especially the mass content of at least one of the cyclic carbonate and the linear carbonate, was adjusted in Examples 5-1 to 5-7.

[0288] Example 6-1 to Example 6-4

[0289] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that at least the composition of the electrolyte, especially the mass content of the fluorinated cyclic carbonate, was adjusted in Examples 6-1 to 6-4.

[0290] Example 7

[0291] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that in Example 7, at least the composition of the electrolyte, especially the type of fluorinated cyclic carbonate, was adjusted to DFEC. DFEC contains two fluorine atoms and has relatively weak polarity, making it more difficult to form a film than FEC.

[0292] Example 8-1 to Example 8-4

[0293] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that in Examples 8-1 to 8-4, at least the liquid retention coefficient of the electrolyte was adjusted.

[0294] Example 9-1 to Example 9-4

[0295] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that at least one of the coating thickness and the porosity in the isolation membrane was adjusted in Examples 9-1 to 9-4.

[0296] Example 9-3 and Example 9-4 use PP materials with different porosities, and the different porosities can be regulated by methods known to those skilled in the art.

[0297] The parameters of the embodiments and comparative examples are shown in Tables 1 to 3.

[0298] Performance Testing

[0299] 1. Lithium-ion DC internal resistance DCR test

[0300] Capacity testing process:

[0301] Under 25°C environment, the lithium ion batteries prepared in the examples and comparative examples were first discharged to 2.8V at 0.33C, then charged to 4.35V at 0.33C, and charged at a constant voltage at 4.35V until the current value was less than 0.05C, and then discharged to 2.8V at 0.33C. The discharge capacity at this time was recorded as the real capacity D0 of the battery;

[0302] 10% SOC adjustment:

[0303] The lithium-ion battery is charged at 0.1C (C at this time is determined by the D0 measured) for 6 minutes to 10% SOC, and the voltage value at this time is recorded as U1; it is discharged at a rate of 4C for 10s, and the voltage value at this time is recorded as U2.

[0304] DC internal resistance DCR = (U1-U2) / I.

[0305] Test Results

[0306] The test results are shown in Tables 1 to 3.

[0307] Table 1

[0308]

[0309] Table 2

[0310]

[0311] Table 3

[0312]

[0313] From Tables 1 to 3, we can see that

[0314] Comparative Examples 1 and 4 both use a suitable electrolyte system, but the mass content of silicon in Comparative Example 1 is relatively high. Even if the system contains a high content of lithium hexafluorophosphate, it cannot well alleviate the volume expansion of silicon-based materials. The silicon-based materials have a high risk of structural collapse, cracking and pulverization, which is not conducive to improving DCR, and the battery discharge power is poor. Comparative Example 4 uses artificial graphite as the negative electrode active material. At low SOC, artificial graphite is difficult to participate in discharge, which easily leads to insufficient discharge and poor discharge power.

[0315] Comparative Examples 2 and 3 both use appropriate silicon material systems, but Comparative Example 2 uses a relatively low content of lithium hexafluorophosphate (12%). The low content of lithium hexafluorophosphate generates relatively few fluorinated lithium compounds on the surface of the negative electrode active material, which cannot effectively alleviate the problem of cracking and pulverization of silicon-based materials; Comparative Example 3 uses a relatively high content of lithium hexafluorophosphate (23%). Although the high content of lithium hexafluorophosphate can effectively alleviate the volume expansion of silicon-based materials, the lithium hexafluorophosphate causes the viscosity of the electrolyte system to be too high, which is not conducive to the migration of lithium ions from the negative electrode surface to the positive electrode surface. In the later stage of discharge, it is difficult to increase the discharge power.

[0316] Compared with Comparative Examples 1 to 4, Example 1 reduces the internal resistance of the battery at the end of discharge and improves the discharge power performance by regulating the silicon content in the negative electrode active material silicon oxide (the mass content of silicon element is not less than 0.3% and less than or equal to 3.0%) and matching it with a suitable electrolyte system (the mass content of lithium hexafluorophosphate is 15% to 20%).

[0317] As the silicon content changes, it has a certain impact on the discharge power of the battery. If the amount of silicon added is small, the negative electrode active material involved in the later discharge is relatively small, which is not conducive to the improvement of the battery discharge power. If the amount of silicon added is large, the adverse effect of volume expansion gradually manifests; therefore, choosing a suitable silicon content is more conducive to the improvement of the battery discharge power. For example, the mass content of silicon in silicon oxide is not less than 0.3% and less than or equal to 3.0%, which can significantly improve the improvement of the battery discharge power. The material of silicon-based materials and carbon-based materials also has a certain impact on the discharge power. The composition of the electrolyte also has a certain impact on the discharge power.

[0318] Example 10-1

[0319] 1. Preparation of positive electrode sheet

[0320] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer. The positive electrode current collector is an aluminum foil with a thickness of 12μm. The positive electrode film layer is formed by evenly coating the positive electrode slurry (solvent is N-methylpyrrolidone NMP) on the surface of the positive electrode current collector aluminum foil, drying, and cold pressing. The positive electrode film layer includes a positive electrode active material, a conductive agent carbon black, and a binder polyvinylidene fluoride (PVDF) in a weight ratio of 97.5:1.4:1.1. The compacted density of the positive electrode film layer is 3.35g / cm 3 .

[0321] The positive electrode active material is a single crystal structure, which includes a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) O zThe compound, wherein the nickel-cobalt-manganese oxide matrix in the positive electrode active material includes a molecular formula of LiNi 0.70 Co 0.10 Mn 0.20 O2 compound. M elements include 450ppm Ti element, 1700ppm Zr element, 1600ppm Al element and 120ppm (B, S and P) element.

[0322] 2. Preparation of negative electrode sheet

[0323] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer. The negative electrode current collector is a copper foil with a thickness of 4.5 μm. The negative electrode film layer includes a film layer formed by uniformly coating a negative electrode slurry (the solvent is deionized water) on the surface of the negative electrode current collector copper foil, drying, and cold pressing. The negative electrode film layer includes a negative electrode active material, a binder styrene-butadiene rubber (SBR), a thickener sodium carboxymethyl cellulose (CMC-Na), and a conductive agent carbon black (Super P) in a weight ratio of 96.2:1.8:1.2:0.8.

[0324] The negative electrode active materials include artificial graphite and silicon-carbon composites.

[0325] 3. Isolation film

[0326] The isolation membrane can be purchased directly from the isolation membrane supplier. The isolation membrane has a porosity of 30%, and the isolation membrane includes an organic substrate (porous polypropylene PP (7 μm)) and a coating, the coating includes a ceramic layer (1 μm) and a polyacrylate layer (1 μm), the ceramic layer is arranged on both surfaces of the organic substrate, the ceramic layer includes a film layer formed by dissolving a binder and inorganic aluminum oxide in N-methylpyrrolidone NMP and coating the organic substrate, the polyacrylate layer is arranged on the surface of the ceramic layer away from the organic substrate, and the polyacrylate layer is a film layer formed by coating a substance containing polyacrylates on the surface of the ceramic layer.

[0327] 4. Preparation of electrolyte

[0328] The electrolyte includes an organic solvent, a lithium salt and an additive. The organic solvent includes cyclic carbonates (EC, PC and BC, the mass ratio of each component is 1:1:1) and linear carbonates (EMC, DMC and DEC, the mass ratio of each component is 1:1:1); the additive includes 0.25% fluorinated cyclic carbonate FEC, the lithium salt includes 18.2% lithium hexafluorophosphate, 0.2% lithium difluorophosphate, and 0.2% lithium tetrafluoroborate, the total content of the lithium salt is 18.6%, and the rest is organic solvent.

[0329] 5. Preparation of batteries

[0330] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained, and the liquid retention coefficient of the lithium-ion battery is 1.3g / Ah.

[0331] Example 10-2 to Example 10-4

[0332] A lithium-ion battery was prepared by a method similar to that of Example 10-1. The difference from Example 10-1 was that the content of each negative electrode active material in the negative electrode sheet was adjusted.

[0333] Example 11 and Example 11-2

[0334] A lithium-ion battery was prepared by a method similar to that of Example 10-1. The difference from Example 10-1 was that the mass content of the fluorinated cyclic carbonate FEC in the electrolyte was adjusted.

[0335] The test methods in Tables 1 to 3 were used for testing, and the test results are shown in Table 4.

[0336] Table 4

[0337]

[0338] As shown in Table 4, Examples 10-1 to 11-2 can significantly reduce the internal resistance of the battery at the end of discharge and improve the discharge power performance by regulating the silicon content (the mass content of silicon in the silicon-carbon composite is not less than 0.3% and less than or equal to 10%) and matching a suitable electrolyte system (the mass content of lithium hexafluorophosphate is 15% to 20%). By regulating the mass content of the fluorinated cyclic carbonate, the internal resistance of the battery at the end of discharge can be adjusted and the discharge power performance can be improved.

[0339] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A battery cell, comprising: An electrolyte, comprising a lithium salt and a fluorinated cyclic carbonate, wherein the lithium salt comprises lithium hexafluorophosphate, and the mass content of the lithium hexafluorophosphate relative to the total mass of the electrolyte is 15% to 20%; the ratio of the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte to the mass content of the silicon element is (0.01 to 0.15):1; A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material; A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and containing a negative electrode active material, wherein the negative electrode active material further comprises a carbon-based material and a silicon-carbon composite, wherein the mass content of silicon in the silicon-carbon composite relative to the total mass of the negative electrode active material is greater than 4% and less than 4.5%; and The separator is arranged between the positive electrode sheet and the negative electrode sheet.

2. The battery cell according to claim 1, wherein: The mass content of the silicon-carbon composite is 0.4% to 14.5% based on the total mass of the negative electrode active material.

3. The battery cell according to claim 2, wherein: The mass content of the silicon-carbon composite is 5.75% to 10% based on the total mass of the negative electrode active material.

4. The battery cell according to any one of claims 1 to 3, wherein: The carbon-based material includes at least one of artificial graphite and natural graphite.

5. The battery cell according to claim 4, wherein: The carbon-based material includes artificial graphite.

6. The battery cell according to any one of claims 1 to 3, wherein: The electrolyte further includes a cyclic carbonate, and based on the total mass of the electrolyte, the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is (0.60 to 2.50):

1.

7. The battery cell according to claim 6, wherein: The ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is (1.00 to 1.65):

1.

8. The battery cell according to claim 6, wherein: The mass content of the cyclic carbonate is 10% to 41%; and / or The cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate and butylene carbonate.

9. The battery cell according to claim 8, wherein: The mass content of the cyclic carbonate is 20% to 30%.

10. The battery cell according to claim 6, wherein: The electrolyte further includes a linear carbonate, and based on the total mass of the electrolyte, the ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate is (0.9 to 6):

1.

11. The battery cell according to claim 10, wherein: The ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate is (1.5 to 2.65):

1.

12. The battery cell according to claim 10, wherein: The mass content of the linear carbonate is 35% to 65%; and / or The linear carbonate includes at least one of ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate.

13. The battery cell according to any one of claims 1 to 3, wherein: The electrolyte also includes a fluorinated cyclic carbonate.

14. The battery cell according to claim 13, wherein: The fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate, bisfluoroethylene carbonate and trifluoropropylene carbonate.

15. The battery cell according to claim 14, wherein: The fluorinated cyclic carbonate includes monofluoroethylene carbonate.

16. The battery cell according to claim 13, wherein: Based on the total mass of the electrolyte, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.005 to 0.30):

1.

17. The battery cell according to claim 16, wherein: Based on the total mass of the electrolyte, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.005 to 0.03):

1.

18. The battery cell according to claim 13, wherein: The mass content of the fluorinated cyclic carbonate is 0.05% to 5.80% based on the total mass of the electrolyte.

19. The battery cell according to claim 18, wherein: The mass content of the fluorinated cyclic carbonate is 0.1% to 1.0% based on the total mass of the electrolyte.

20. The battery cell according to any one of claims 1 to 3, wherein: The lithium salt further comprises at least one of a fluorine-containing inorganic phosphate and a fluorine-containing inorganic borate.

21. The battery cell according to claim 20, wherein: Based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic phosphate is 0.05% to 0.50%; and / or Based on the total mass of the electrolyte, the mass content of the fluorine-containing inorganic borate is 0.05% to 0.50%.

22. The battery cell according to claim 21, wherein: The mass content of the fluorine-containing inorganic phosphate is 0.10% to 0.30%; and / or The mass content of the fluorine-containing inorganic borate is 0.10% to 0.30%.

23. The battery cell according to claim 21, wherein: The fluorine-containing inorganic phosphate comprises lithium difluorophosphate LiPO2F2; and / or The fluorine-containing borate includes at least one of lithium tetrafluoroborate LiBF4 and lithium difluorooxalatoborate LiDFOB.

24. The battery cell according to any one of claims 1 to 3, wherein: The battery cell has a liquid retention coefficient of 1.0 g / Ah to 2.5 g / Ah.

25. The battery cell according to claim 24, wherein: The battery cell has a liquid retention coefficient of 1.0 g / Ah to 1.5 g / Ah.

26. The battery cell according to any one of claims 1 to 3, wherein: The porosity of the isolation film is 30% to 40%.

27. The battery cell according to any one of claims 1 to 3, wherein: The isolation film includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating includes a heat-resistant layer and an organic layer, the heat-resistant layer is disposed on the surface of the organic substrate, and the organic layer is disposed on the surface of the heat-resistant layer away from the organic substrate.

28. The battery cell according to claim 27, wherein: The organic layer includes a non-fluorinated polymer.

29. The battery cell according to claim 28, wherein: The non-fluoropolymer includes a polyacrylate layer.

30. The battery cell according to claim 27, wherein: The thickness of the organic substrate is 6.6 μm to 7.6 μm; and / or The coating has a thickness of 1.5 μm to 2.5 μm.

31. The battery cell according to any one of claims 1 to 3, wherein: The positive electrode active material includes a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) Y z A compound wherein 0<d≤2.1, 0.6<a<1, 0<b<1, 0<c<1, and 0.6<a+b+c<1, 1.8≤z≤3.5, the M element includes at least one of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and the Y element includes at least one of O and F.

32. The battery cell according to claim 31, wherein: 0.85≤a≤0.95。 33. The battery cell according to claim 31, wherein: The positive electrode active material includes at least one of single crystal particles and polycrystalline particles.

34. The battery cell according to claim 33, wherein: The positive electrode active material includes single crystal particles and polycrystalline particles.

35. A battery comprising the battery cell according to any one of claims 1 to 34.

36. An electrical device comprising the battery as claimed in claim 35.

Citation Information

Patent Citations

  • Battery monomer, battery and electric device

    CN117154187A

  • Lithium ion battery, battery and electric device

    CN117154188A

  • Negative active material, negative plate and lithium ion battery

    CN117936722A

  • Lithium ion battery, battery and electric device

    CN118435407A